Amazing Beauties - New Straits Times (2008)
Undergraduates Oh Puey Fong and Zana joelle Chin right were crowned Miss Malaysia Model of the World 2008 and Miss Malaysia International Model of the Year 2008 respectively in a two in one pageant in Ipoh on Sunday night. The girls beat 21 others in a nationwide contest organised by Marigold HL Low Fat Milk and Star Avenue Production. Oh 23 wowed the crowd with her elegant catwalk when she paraded in the swimwear casual and evening gown rounds. Meanwhile Universiti Putra Malaysia first year business student Zana 20 stole the audience s heart when she performed excellently in imitating a talent test.